Combating financial crimes through forensic accounting in Nigerian public sector (Journal of Economic Research & Business Administration, 2020)
Financial crimes are a global issue which remains unresolved. These crimes have plagued everycorner of the world economy. The adverse effect of these crimes is immense in Nigeria. Continuousresearch confirmed a strong demand for the forensic accounting of preventing, detecting and arrestingof financial crimes menace in Nigeria and the rest of the world. However, the studies of combatingfinancial crimes through forensic accounting are very few in literature and not fully explored in Nigerianpublic sector. This study therefore, sets to examine the impact of forensic accounting techniquesfor combating financial crimes in Nigerian public sector. This study employs a survey research designand purposive sampling technique to select the sample of eighty six (86) accountants and auditors ofthe three selected ministries in Osun State, Nigeria. Both primary and secondary data were collected.The primary data was collected through a designed structured questionnaire. The data collected wasanalyzed using descriptive and inferential statistical tools. It was found that combating of financialcrimes in Nigerian public sector through the application of forensic accounting is possible as the p–value = 0.00 < 0.01. This study therefore concluded that, government of Nigeria should increase theinterest in and facilitate the growth of forensic accounting by giving legal backing for proper monitoryand investigation of alleged cases of financial crimes. This study recommended that, all governmentministries, agencies and parastatals should establish forensic accounting unit to help strengthen internalcontrols and ensure thorough investigation in order to prevent, deter and detect financial crimesand the University regulatory body as well as the accounting professional bodies should ensure thatforensic accounting courses are included in the curricula to ensure the training and increased awarenessof forensic accounting in Nigeria.